Boosting the Capacity of Aqueous Li‐Ion Capacitors via Pinpoint Surgery in Nanocoral‐Like Covalent Organic Frameworks. Issue 8 (12th June 2022) - Geng, Qianhao; Wang, Haichao; Wang, Jinlong; Hong, Jie; Sun, Weiwei; Wu, Yang; Wang, Yong
Abstract: Aqueous lithium storage devices are promising candidates for next‐generation energy storage applications, featuring low‐cost, safety, environmental benignness, and grid‐scale merits. Developing reliable anode materials with fast Li + diffusion is paramount to stimulate their development. Herein, the electrochemical performance and mechanism of a redox‐active β‐ketoenamine‐linked covalent organic framework (COF) (2, 6‐diaminoanthraquinone and 2, 4, 6‐triformylphloroglucinol COF, DAAQ–TFP–COF) for lithium storage in aqueous electrolyte are explored for the first time. Systematic studies demonstrate that, by the conversion of neutral COF into anionic COF via a pinpoint surgery on the β‐ketoenamine linkage, the resultative COF shows doubled Li + storage capacity (132 mAh g −1 at 0.5 A g −1, 87% of theoretical specific capacity), good rate capability (108 mAh g −1 at 10 A g −1 ), and excellent cyclability in 1000 cycles. This pinpoint surgery can be promising in extending the electrochemical applications of β‐ketoenamine‐linked COFs. The Li + storage mechanism is investigated by ex situ electron paramagnetic resonance, in situ / ex situ Fourier transform infrared investigations, and density functional theory calculations. As a proof of new concept, a novel aqueous lithium‐ion capacitor assembled with DAAQ–TFP–COF anode delivers high specific capacitance of 224 F g −1 (0.1 A g −1 ), supercapacitor‐level power density (≈4000 W kg −1 ), and long cyclability. Abstract : The strategy of converting the neutral covalent organic framework (COF) into anionic COF via a pinpoint surgery on the β‐ketoenamine linkage is developed to improve the electrochemical performances of a redox‐active covalent organic framework (2, 6‐diaminoanthraquinone and 2, 4, 6‐triformylphloroglucinol COF, DAAQ–TFP–COF) as an anode for lithium‐ion storage in aqueous electrolyte for the first time.